Nitric Oxide Functions as a Downstream Signal for Melatonin-Induced Cold Tolerance in Cucumber Seedlings - Feng, Yiqing; Fu, Xin; Han, Lujie; Xu, Chenxiao; Liu, Chaoyue; Bi, Huangai; Ai, Xizhen (Frontiers in Plant Science, 2021)
Melatonin (MT) and nitric oxide (NO) are two multifunctional signaling molecules that are involved in the response of plants to abiotic stresses. However, how MT and NO synergize in response to cold stress affecting plants is still not clear. In this study, we found that endogenous MT accumulation under cold stress was positively correlated with cold tolerance in different varieties of cucumber seedlings. The data presented here also provide evidence that endogenous NO is involved in the response to cold stress. About 100 μM MT significantly increased the nitrate reductase (NR) activity, NR-relative messenger RNA (mRNA) expression, and endogenous NO accumulation in cucumber seedlings. However, 75 μM sodium nitroprusside (SNP, a NO donor) showed no significant effect on the relative mRNA expression of tryptophan decarboxylase (TDC), tryptamine-5-hydroxylase (T5H), serotonin-N-acetyltransferase (SNAT), or acetylserotonin O-methyltransferase (ASMT), the key genes for MT synthesis and endogenous MT levels. Compared with H2O treatment, both MT and SNP decreased electrolyte leakage (EL), malondialdehyde (MDA), and reactive oxygen species (ROS) accumulation by activating the antioxidant system and consequently mitigated cold damage in cucumber seedlings. MT and SNP also enhanced photosynthetic carbon assimilation, which was mainly attributed to an increase in the activity and mRNA expression of the key enzymes in the Calvin–Benson cycle. Simultaneously, MT- and SNP-induced photoprotection for both photosystem II (PSII) and photosystem I (PSI) in cucumber seedlings, by stimulating the PsbA (D1) protein repair pathway and ferredoxin-mediated NADP+ photoreduction, respectively. Moreover, exogenous MT and SNP markedly upregulated the expression of chilling response genes, such as inducer of CBF expression (ICE1), C-repeat-binding factor (CBF1), and cold-responsive (COR47). MT-induced cold tolerance was suppressed by 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (cPTIO, a specific scavenger of NO). However, p-chlorophenylalanine (p-CPA, a MT synthesis inhibitor) did not affect NO-induced cold tolerance. Thus, novel results suggest that NO acts as a downstream signal in the MT-induced plant tolerance to cold stress.